Constitutional-Legal and Political Responsibility of Political Parties in the Russian Federation to Electors - Gutorova, Alla N.; Andreev, Sergey D.; Arutyunyan, Tatyana I.; Korovin, Vladimir V.; Troyan, Vlalimir A. (Cuestiones Políticas, 2020)
The processes of development of government institutions in the Russian Federation have required the introduction of new mechanisms of legal responsibility of subjects of power relations in legislation. In recent times, the most significant practical interest is the problem of the early termination of the exercise of power of elected officials in legislative positions. The objective of the article is therefore to analyze the legal and political responsibility of the officials of the democratically elected state before their voters. In the process on the subject of the study, the formal-legal and comparative-legal methods were used, which allowed to formulate the following conclusions. The subjects of the above responsibility may be elected officials of the legislative (representative) bodies of state power. The constitutional status of elected persons exercising public authority on behalf of individuals suggests the possibility of terminating their powers as sanctions only on the basis of the rules of law enshrined in the relevant acts and establishing clear reasons and procedures for liability. The current legislation of the Russian Federation provides for various types of constitutional and legal sanctions. They consist of depriving elected officials of their powers.